2022
DOI: 10.3390/biomedicines10082001
|View full text |Cite
|
Sign up to set email alerts
|

Do Apixaban Plasma Levels Relate to Bleeding? The Clinical Outcomes and Predictive Factors for Bleeding in Patients with Non-Valvular Atrial Fibrillation

Abstract: Apixaban can significantly prevent stroke events in patients with non-valvular atrial fibrillation (NVAF), as can be observed from the large, randomized, controlled trial conducted in the present study. However, the real-world evidence of bleeding events related to the apixaban plasma levels in Asian populations is limited. This study aimed to investigate the apixaban plasma levels and clinical outcomes among NVAF patients receiving apixaban, including determining the risk factors associated with bleeding duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…DOAC concentrations are related to effect. Higher concentrations have been associated with bleeding events [ 33 ], while lower concentrations appear to predispose to the occurrence of strokes [ 34 ], albeit a therapeutic range for DOAC concentrations remains to be defined [ 35 ]. A number of factors can contribute to impaired drug clearance such as renal and liver impairment, sarcopenia, and hypoalbuminemia, many of which are present in frail patients [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…DOAC concentrations are related to effect. Higher concentrations have been associated with bleeding events [ 33 ], while lower concentrations appear to predispose to the occurrence of strokes [ 34 ], albeit a therapeutic range for DOAC concentrations remains to be defined [ 35 ]. A number of factors can contribute to impaired drug clearance such as renal and liver impairment, sarcopenia, and hypoalbuminemia, many of which are present in frail patients [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our previous analyses [ 7 , 8 ], there were significantly higher rivaroxaban levels at the time of bleeding compared to the trough levels of patients who did not have complications during rivaroxaban administration (245.9 ± 150.2 ng/mL versus 52.5 ± 36.4 ng/mL; p < 0.001), and rivaroxaban levels tended to be lower in those experiencing embolic stroke (42.7 ± 31.9 ng/mL); however, the variability in drug plasma levels was the highest in rivaroxaban-treated patients. For apixaban, Limcharoen et al [ 22 ] reported an association between apixaban trough levels and the risk of bleeding. In apixaban-treated patients with bleeding, apixaban trough levels of 139.15 ng/mL were reported.…”
Section: Optimal Doac Plasma Levels For Long-term Anticoagulationmentioning
confidence: 99%
“…These levels are lower than our previous observation of apixaban levels of 311.8 ± 142.5 ng/mL at the time of a bleeding event [ 7 ]. It is interesting that, in the study performed by Limcharoen et al, almost all the patients presented apixaban plasma levels within the expected range, which was defined as a range of 34.0–230.0 ng/mL for trough and 69.0–321.0 ng/mL for peak drug levels [ 22 ]. The ranges were derived from a pharmacokinetic study with apixaban [ 23 ].…”
Section: Optimal Doac Plasma Levels For Long-term Anticoagulationmentioning
confidence: 99%